Pengembangan Strategi Mind Mapping dalam Bimbingan Kelompok untuk Meningkatkan Wawasan Karir Siswa Kelas XI SMK Pratama Widya Mandala Badung Tahun 2026 - Kusuma Wardani; I Gusti Lanang Rai Arsana; Putu Agus Semara Putra Giri (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
This study aimed to develop a mind mapping strategy within group guidance services to enhance the career awareness of eleventh-grade students at SMK Pratama Widya Mandala Badung in 2026. The study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The product developed was a group guidance service manual based on the mind mapping strategy, designed to assist students in understanding their potential, exploring the world of work, and planning their careers systematically.The product was tested on four students who demonstrated low levels of career awareness. Data were collected through expert validation, questionnaires, observations, and pre-test and post-test assessments. The findings revealed an improvement in students’ career awareness scores after participating in the group guidance service. The average N-Gain score was 0.79, which falls into the high category, while students’ responses to the product achieved a percentage score of 89.5%, indicating a highly feasible category. The results demonstrate that the mind mapping strategy implemented in group guidance services is both feasible and effective in improving the career awareness of vocational high school students. Therefore, the developed product can serve as an alternative guidance and counseling service to support students in developing a better understanding of career planning and future career opportunities.